FEATURES OF METHODS OF TEACHING OPERATING SYSTEMS AT THE UNIVERSITY - Bidaybekov, Е.Ы.; Grinshkun, В.В.; Koneva, С. Н.; Gaziz, Г.Г. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article analyzes the methods used in the process of teaching the operating system to enable students to understand the role of the operating system and master its principle, to teach students abstract thinking and problem solving skills. The analysis shows that the developed methods have features that occur during training. This allows students to easily understand the principle of operation and to some extent understand the role of the operating system. Together with the teaching experience, the author highlighted the features of theoretical training and practical (experimental) training in two aspects of the development of the operating system, and also demonstrated comparative results of indicators of the effectiveness of using methods over the last 3 years of training.